2018
DOI: 10.18393/ejss.336816
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of infiltration from soil hydraulic properties

Abstract: Field and laboratory infiltration measurements using infiltrometers have been the only methods of effectively determining the infiltration rates of soils. Infiltration is mainly controlled by soil hydraulic properties, especially the hydraulic conductivity. Due to the ease with which the saturated hydraulic conductivity can be determined, it is often preferred to the unsaturated hydraulic conductivity in hydrological studies. It is well known that, at saturation the steady state infiltrability controls the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Patil et al [24] observed that soil infiltration capacity was a key parameter influencing the occurrence of soil hydrologic response hence its spatial variability at different agricultural plots is important to for water resource planning and designing of hydraulic structures. Infiltration capacity is controlled by soil hydraulic properties and field and laboratory measurement are the only effective ways of its determination [27]. Information on how the land use types affects on-site hydrologic response and generation of stream flow is scanty in the URiNC.…”
Section: Introductionmentioning
confidence: 99%
“…Patil et al [24] observed that soil infiltration capacity was a key parameter influencing the occurrence of soil hydrologic response hence its spatial variability at different agricultural plots is important to for water resource planning and designing of hydraulic structures. Infiltration capacity is controlled by soil hydraulic properties and field and laboratory measurement are the only effective ways of its determination [27]. Information on how the land use types affects on-site hydrologic response and generation of stream flow is scanty in the URiNC.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, Ksat represents the limiting value of infiltration if the soil is saturated and homogenous (Arrington et al, 2013). In fact, Ksat can be substituted for Io in equations for infiltration estimates in Ghana (Tuffour et al, 2018). Similarly, soil water infiltration modelled by I = Ksat were close to those modelled by Parlange model under ponding conditions (Dejun & Zhengfu, 2011).…”
Section: Appendix A1mentioning
confidence: 79%
“…Infiltration modelling using measurable soil hydraulic parameters is essential for obtaining these infiltration rates. A number of predictive infiltration models were developed to estimate infiltration rates (Tuffour et al, 2018). The four most commonly adopted models in applied hydrology are the Philip model, the Green-Ampt model, the Smith model and the Parlange model (Morbidelli et al, 2018;Tuffour et al, 2019).…”
Section: Appendix A1mentioning
confidence: 99%
See 1 more Smart Citation